Deep Femoral Vein Reconstruction for Abdominal Aortic Graft Infections is Associated with Low Aneurysm Related Mortality and a High Rate of Permanent Discontinuation of Antimicrobial Treatment. (December 2021) - Langenskiöld, Marcus; Persson, Sven-Erik; Daryapeyma, Alireza; Gillgren, Peter; Hallin, Anders; Hultgren, Rebecka; Jonsson, Magnus; Nordanstig, Joakim
Abstract : Objective: Aortic prosthesis infection is a devastating complication of aortic surgery. In situ reconstruction with the neo-aorto-iliac system (NAIS) bypass technique has become increasingly used and is recommended in recent treatment guidelines. The main aim was to evaluate NAIS procedural outcomes when undertaken after previous open or endovascular aortic repair in Sweden. Methods: In this retrospective study, The National Quality Registry for Vascular Surgery (Swedvasc) was used to identify Swedish centres that offered the NAIS bypass procedure for aortic prosthesis infection between 2008 and 2018. Variables of special interest were procedural details, short and long term survival, renal and other complications, and the durtion of antimicrobial treatment. Results: Forty patients (36 males, four females [mean age 69 years], 32 open repairs, seven endovascular aortic repairs [EVAR] and one fenestrated EVAR; 21 presented with aorto-enteric fistula) operated on with NAIS bypass were reviewed. The median time from the primary aortic intervention to the NAIS bypass procedure was 32 months (range 0 – 252 months). Mean ± standard deviation operating time was 645 ± 160 minutes, mean blood loss was 6 277 ± 6 525 mL, mean length of intensive care unit stay was 5.3 ± 3.7 days, and mean length of overall hospital stay was 21.2 ± 11.4 days. Thirty-five patients (88%) had a positive microbial culture; the most commonly isolated pathogen was Candida spp. The majority of patients survived for 30 days ( n  = 35 [88%]), and 33 (83%) and 32 (80%) patients survived for 90 days and one year, respectively. The number of surviving patients free from antimicrobial treatment at 90 days, six months, and one year was 19 (58%), 29 (88%), and 30 (94%). After a mean long term follow up of 69.9 ± 44.7 months, 20 patients were still alive. Conclusion: The NAIS bypass procedure offered reasonable survival and functional outcomes, and was associated with a high cure rate, defined as freedom from any antimicrobial treatment.